The Effect of Institutional Ownership on Investment Efficiency with Accounting Conservatism as a Mediator in Non-Financial Companies on the Indonesia Stock Exchange - Razki, Cut Danisha; Arfan, Muhammad; Saputra, Mulia (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study investigates how institutional ownership influences investment efficiency, using accounting conservatism as an intermediary factor, the study examines non-financial firms listed on the Indonesia Stock Exchange for the period from 2018 to 2020. The sample comprises 102 firms chosen via stratified random sampling. Annual report data from the companies were assessed through path analysis, revealing that institutional ownership positively influences accounting conservatism, which in turn positively affects investment efficiency. However, institutional ownership alone does not significantly impact investment efficiency. Accounting conservatism has been shown to mediate the connection between institutional ownership and investment efficiency.